The dogmatic customer as a mediating variable between brand trust and marketing inspiration. - Al-Taee, Yousif Hchaim; Kashkooul, Hussein Muhammad Ali (CV. Bimbingan Belajar Assyfa, 2023)
The general objective of this study is to identify the importance of the dogmatic customer as a mediating variable between trust in the brand to achieve marketing inspiration. Among the recent topics as an independent explanatory variable, marketing inspiration as a responding variable, and the dogmatic customer as a mediating variable between them, the analysis was carried out by adopting a set of statistical tools that are commensurate with the purpose of the study, and the two statistical package programs (Smart PLS) were adopted, and the research included a number of conclusions: that the dogmatic customer The great impact on the unique and introverted behavior and that his ideas that he received from his narrow knowledge society towards building marketing inspiration for organizations. The research presented a set of recommendations based on the results that were reached.